Introducing galactic structure finder: the multiple stellar kinematic structures of a simulated Milky Way mass galaxy. Issue 4 (21st April 2018) - Obreja, Aura; Macciò, Andrea V; Moster, Benjamin; Dutton, Aaron A; Buck, Tobias; Stinson, Gregory S; Wang, Liang
Abstract: We present the first results of applying Gaussian Mixture Models in the stellar kinematic space of normalized angular momentum and binding energy on NIHAO high-resolution galaxies to separate the stars into multiple components. We exemplify this method, using a simulated Milky Way analogue, whose stellar component hosts thin and thick discs, classical and pseudo bulges, and a stellar halo. The properties of these stellar structures are in good agreement with observational expectations in terms of sizes, shapes, and rotational support. Interestingly, the two kinematic discs show surface mass density profiles more centrally concentrated than exponentials, while the bulges and the stellar halo are purely exponential. We trace back in time the Lagrangian mass of each component separately to study their formation history. Between z  ∼ 3 and the end of halo virialization, z  ∼ 1.3, all components lose a fraction of their angular momentum. The classical bulge loses the most (${\sim }95\hbox{ per cent}$ ) and the thin disc the least (${\sim }60\hbox{ per cent}$ ). Both bulges formed their stars in situ at high redshift, while the thin disc formed ${\sim }98\hbox{ per cent}$ in situ, but with a constant SFR  ∼ 1.5 M⊙  yr −1 over the last ∼11 Gyr. Accreted stars ($6\hbox{ per cent}$ of total stellar mass) are mainly incorporated to the thick disc or the stellar halo, which formed ex situ $8\hbox{ per cent}$ and $45\hbox{ per cent}$ of their respective masses. Our analysis pipeline is freely available at https://github.com/aobr/gsf .